New approaches to the temple of Zeus at Olympia: proceedings of the First Olympia-Seminar, 8th-10th May, 2014 - Patay-Horváth, András (Cambridge Scholars Publishing, 2015)
This volume brings together the proceedings of an international and interdisciplinary symposium held at Budapest between 8th and 10th May 2014. It was the first event dealing exclusively with the temple of Zeus at Olympia, which was, at the time of its construction, the largest temple in mainland Greece, and which has remained the largest ancient building of the Peloponnese ever since. Contributors come from eight countries, namely Austria, France, Germany, Greece, Hungary, Italy, Japan, and the UK, and from several different fields of classical studies, including archaeology, ancient history, numismatics, epigraphy and architecture. The contributions deal with widely different aspects of the building and its sculptural decoration, including masons' marks, metrology, the usage of different marbles, and depictions of invisible gods, and approach these issues from new and unique perspectives. Some papers focus on the cult of Zeus, or on inscriptions found in or on coins associated with the sanctuary; others describe how later authors might have used the monument, or bridge the gap between classical studies and the latest digital technologies applied to archaeology and cultural heritage. As such, all of the essays gathered here will inspire classical scholars to make use of these new research paths
Keywords: Zeus *(Greek deity)* -- Cult -- Congresses; Temple of Zeus (Olympia, Greece) -- Congresses; Olympia (Greece : Ancient sanctuary) -- Congresses -- Olympia (Greece : Ancient sanctuary) -- Temple of Zeus (Olympia, Greece); Archaia Olympia (Greece) -- Congresses -- History -- Greece -- Archaia Olympia; Greece -- Antiquities -- Congresses; Konferenzschrift -- 2014 -- Budapest; Zeustempel